2002
DOI: 10.1152/ajpheart.00845.2001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anesthesia on cardiac function during echocardiography in mice

Abstract: Anesthetics provide sedation and immobility facilitating echocardiography in mice, but influence cardiac function. We studied the effects of intraperitoneal and inhaled anesthetic agents on echocardiographic measurements. Mice were anesthetized with intraperitoneal tribromoethanol (TBE), ketamine-midazolam (K/M), ketamine-xylazine (K/X), or inhaled isoflurane (Isf), and echocardiographic parameters were assessed at 5, 10, 15, and 20 min. In C57BL/6N mice, Isf produced high initial heart rates (HR) that decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
251
6
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(278 citation statements)
references
References 22 publications
17
251
6
4
Order By: Relevance
“…Isoflurane anesthesia is known to decrease hearts rates and contractility in mice, so our study showed lower heart rates and decreased overall percent shortening fraction. [23] Although the variability in heart rates seen with anesthesia can affect calculated values such as cardiac output, the effects on shortening fraction are consistent between groups. The decrease in cardiac ventricular function corresponded with a significant increase in the left ventricular end systolic dimension.…”
Section: Discussionmentioning
confidence: 84%
“…Isoflurane anesthesia is known to decrease hearts rates and contractility in mice, so our study showed lower heart rates and decreased overall percent shortening fraction. [23] Although the variability in heart rates seen with anesthesia can affect calculated values such as cardiac output, the effects on shortening fraction are consistent between groups. The decrease in cardiac ventricular function corresponded with a significant increase in the left ventricular end systolic dimension.…”
Section: Discussionmentioning
confidence: 84%
“…Regarding the absence of significant respiratory artifacts, its easy regulation, and the fact that isoflurane produces physiologic heart rates and a very stable heart function during anesthesia (33), this anesthetic seems to be superior for studies where its vasodilatoric effect is of minor importance.…”
Section: Discussionmentioning
confidence: 99%
“…The echocardiographer was blinded with respect to the treatment group. To avoid anesthetic-related impairment of cardiac function during echocardiography, 48 examinations were performed on lightly sedated animals using an intraperitoneal injection of 100 mg kg À1 2,2,2-tribromethanol (Sigma). Left ventricular parasternal short-axis views were obtained in M-mode imaging at the papillary muscle level.…”
Section: Echocardiographymentioning
confidence: 99%